Plan de negocios para la creación de la empresa Verner, dedicada a la producción y comercialización de productos cosméticos naturales, dirigido a mujeres del cantón Latacunga, provincia de Cotopaxi. - Yugsi Pastuña, Pamela Elizabeth (2021)
The current cosmetic industry is undergoing an unstoppable evolution because it is no longer a world of promises and illusions, but a science linked to research, innovation and convincing results. In this sense, this project aims to develop a business plan for the creation of the company VERNER dedicated to the manufacture and marketing of natural cosmetic products aimed at latacungueñas´s women, for which projects related to business plans were investigated theoretically, establishing the Canvas business model as the most appropriate for the development of the project. In the market research, the acceptance of VERNER products was determined, obtaining 94% of predisposition to purchase the natural cosmetic product Neem based effervescent bombs with its three presentations, information obtained through the execution of surveys and focus groups applied to the market segment, being a qualitative and quantitative research study, these approaches allowed synthesizing the information and interpreting it, thus estimating a potential unsatisfied demand in the cosmetic market. The technical analysis estimated an installed capacity of 23,040 units per year. Finally, the approximate valuation of the enterprise is $16,486.87, its projection establishes a positive Internal Rate of Return (IRR) and Net Present Value (NPV) demonstrating the viability of the project, contributing to the provincial socioeconomic development, through the generation of sources of employment in the housing complex "Nuevo Amanecer" granted by the program "Casa para todos" in the Pujilí canton.